Talent Development Through Teamwork in a Study Environment - Civić, Aila; Kremsar, Sara; Marič, Miha (Izzivi managementa talentov, 2025)
One of the key skills students develop during their studies is teamwork. This approach enables the discovery and development of individual talents, contributing to better collaboration and the application of knowledge in practice. While talents are often innate, they can also be cultivated through experience. Students frequently discover them only when exposed to various team roles, which are typically assigned based on abilities and strengths. A study involving 65 students revealed that team dynamics occur occasionally to frequently, with students spending an average of 5.2 hours per week on teamwork. The main criteria for forming teams were identified as members’ skills and personal traits. The greatest advantages of teamwork include the development of leadership and communication skills as well as more effective decision-making. The most common drawbacks are uneven task distribution, disagreements, and poor organization. Mentorship and collaboration with companies were recognized as the most effective approaches to improving teamwork.